The elements : a visual exploration of every known atom in the universe - Gray, Theodore W; Mann, Nick (New York : Black Dog & Leventhal Publishers : Distributed by Workman Pub. Co., 2009)
Everything in the world that is tangible is made up of elements, and elements have two faces -- their pure states and the range of chemical compounds they form when they combine with other elements. This book provides the opportunity to see both up close and person. Organized in order of appearance in the periodic table, the book showcases each element (wherever possible) with a photograph of the pure element. Also included are photographs that show examples of the way that element lives in the world -- the compounds and applications in which we experience the element in daily life. The text that accompanies each spread tells the story of the element. Along with the story of each element is essential scientific data including atomic weight, atomic radius, a crystal structure diagram, and graphs representing electron filling order, the atomic emission spectrum, and the temperatures at which the element is a solid, liquid, or gas
Includes bibliographical references (p. 236) and index
Keywords: Chemical elements; Chemical elements -- Pictorial works; Periodic law -- Tables; Pictorial works; Tables